Hubungan bentuk imajinasi dengan kata konkret dalam pantun karya siswa kelas VII SMP - Mujiati, Dwi Sinta; Andalas, Eggy Fajar; Setiawan, Arif (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Junior high school students are taught to write rhymes, which leads to a number of interesting phenomena. This study focused on imagination and concrete words in rhymes written by students. This study aims to describe the relationship between the use of imagination and concrete words chosen by grade VII junior high school students. The method used is qualitative research with a correlational approach, where there are two variables, namely imagination and concrete words that will be analyzed the relationship between the two. At the level of text analysis, the results of the analysis show that there are three imaginations used, namely visual, auditive and tactile imagination while the concrete words used are classified into four, namely concrete words that describe an object, a place, food and drink, and fruits. The results showed a relationship between students' imagination and the use of concrete words in written rhymes. This is influenced by the student's ability to concretize the chosen word. Students who are more imaginative will use concrete words more creatively and create a stronger imagination in student rhymes.